2014
DOI: 10.1016/j.joen.2013.09.031
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Regulation of CCL3 and CXCL12 by Bacterial By-products Is Dependent on Site of Origin of Human Oral Fibroblasts

Abstract: Introduction Production of chemokines by tissue resident cells is one of the main mechanisms involved in the inflammatory infiltrate formation during inflammation. The specific ability of fibroblasts from different oral tissues such as gingiva, periodontal ligament and dental pulp from permanent and deciduous teeth in producing the chemokines CCL3 and CXCL12 under stimulation by bacterial products commonly found in endodontic infections was investigated. Methods Cultures of fibroblasts from gingiva and perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 37 publications
(55 reference statements)
5
31
1
3
Order By: Relevance
“…Cultured cells were characterized as fibroblasts by their morphology and positivity for fibroblast surface protein (FSP)‐1 as previously described 10 , 32 . Immunostaining was performed by using mouse antihuman FSP‐1 (1B10), ‡ followed by fluorescein‐conjugated antimouse immunoglobulin G § .…”
Section: Methodsmentioning
confidence: 99%
“…Cultured cells were characterized as fibroblasts by their morphology and positivity for fibroblast surface protein (FSP)‐1 as previously described 10 , 32 . Immunostaining was performed by using mouse antihuman FSP‐1 (1B10), ‡ followed by fluorescein‐conjugated antimouse immunoglobulin G § .…”
Section: Methodsmentioning
confidence: 99%
“…LPS in infected pulp tissues of pulp canal could activate LYMs and FBs producing pro-inflammatory cytokines such as TNF and IL-1 (Chang et al, 2005). Some studies have suggested that FBs could be activated to secret inflammatory cytokines, such as NLRP3 and IL-33, after stimulation of inflammation and participate in infiltration, cell transport, and tissues fibrosis in the tissue repair process (Liu and Liu, 2013;Sipert et al, 2014;Velickovic et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With written informed consent, teeth and gingival tissues were donated by patients undergoing lower third molar removal. Cultures of human fibroblasts from dental pulp, gingiva and periodontal ligament from the same donors (n = 3) (2 females and 1 male, 16-26 years old) were established by means of the explant technique as described elsewhere (5,7,23). Immediately after removal, the tissues were kept separately under aseptic conditions.…”
Section: Fibroblast Culturementioning
confidence: 99%
“…However, it has been clearly demonstrated that the biological behavior of fibroblasts is related to the type of connective tissue from which they originate (2)(3)(4). Such properties include membrane receptor expression (3) and cytokine release kinetics (2,3,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%